A typology of employers' organisations in the United Kingdom. (February 2020) - Gooberman, Leon; Hauptmeier, Marco; Heery, Edmund
This article examines employers' organisations in the United Kingdom, drawing upon 70 interviews and a new dataset encompassing 447 employers' organisations. The article's contribution is to develop a new typology of employers' organisations capturing their organisational change in the wake of the decline of collective bargaining. It does this by drawing on a conceptualisation of employers' organisations as intermediary organisations before identifying four organisational types: lobbying, service, negotiating and standard-setting employers' organisations. The article also identifies and discusses factors that underlie this pattern of differentiation.